Operation Iceberg's Sea Defense Strategy During the Invasion of Okinawa Island in the Pacific War - Patmi, Sri; Prakoso , Lukman Yudho; Alam, Tasdik Mustika; Aliyah, Yurizki; Soemantri, Asep Iwa (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to analyze the sea defense strategy used in the Iceberg operation to strengthen the defense aspect of the country. The method used in this study is descriptive qualitative. The results showed that (1) the naval blockade was an effective strategy in winning the battle on Okinawa Island, (2) the establishment of a sea defense line in operation Iceberg supported the protection of the Allied fleet towards the Ryukyu Islands from attacks by Japanese submarines and enemy warplanes, (3) Marine aircraft were used in operation iceberg to counter the threat of floating glaciers and to monitor the movement of those glaciers, (4) Cooperation between the Allied fleets of the United States, Great Britain, and Australia in Operation Iceberg was critical to the successful invasion and protecting forces from attacks by the Japanese naval fleet, and (5) Allied forces conducted naval intelligence monitoring around Okinawa Island to monitor the Japanese naval fleet using aerial reconnaissance, radar monitoring, and submarine reconnaissance.